2010
DOI: 10.1111/j.1095-8312.2010.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogeography of four Apodemus species (Mammalia: Rodentia) in the Asian Far East: evidence of Quaternary climatic changes in their genetic structure

Abstract: The phylogeography of four Apodemus species (Apodemus agrarius, Apodemus peninsulae, Apodemus latronum, and Apodemus draco) was studied in the Far East of Asia, based on sequences of the mitochondrial DNA cytochrome b gene. The results obtained show the existence of many different genetic lineages within the studied Apodemus species, suggesting the isolation and differentiation of populations in multiple refuge areas. Higher genetic diversities in some regions such as Yunnan, Sichuan (China), and eastern Russi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 73 publications
(103 reference statements)
4
84
1
Order By: Relevance
“…The present study and Sato et al (2011) suggest that the mtDNA lineage of the sable in Hokkaido was established during the Late Pleistocene. This migration time estimate is consistent with that for the Korean field mouse (Sakka et al 2010), but not with those for the Eurasian flying squirrel, the gray redbacked vole, and the mountain hare, whose migration times were estimated to occur during the late Middle Pleistocene (Yamada et al 2002;Oshida et al 2005;Abramson et al 2012;Kinoshita et al 2012). On the other hand, the brown bear Ursus arctos and the red fox Vulpes vulpes possess several distinctive mtDNA lineages on Hokkaido, suggesting repeated colonizations since the Middle to Late Pleistocene (Matsuhashi et al 1999(Matsuhashi et al , 2001Inoue et al 2007;Korsten et al 2009;Hirata et al 2013).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The present study and Sato et al (2011) suggest that the mtDNA lineage of the sable in Hokkaido was established during the Late Pleistocene. This migration time estimate is consistent with that for the Korean field mouse (Sakka et al 2010), but not with those for the Eurasian flying squirrel, the gray redbacked vole, and the mountain hare, whose migration times were estimated to occur during the late Middle Pleistocene (Yamada et al 2002;Oshida et al 2005;Abramson et al 2012;Kinoshita et al 2012). On the other hand, the brown bear Ursus arctos and the red fox Vulpes vulpes possess several distinctive mtDNA lineages on Hokkaido, suggesting repeated colonizations since the Middle to Late Pleistocene (Matsuhashi et al 1999(Matsuhashi et al , 2001Inoue et al 2007;Korsten et al 2009;Hirata et al 2013).…”
Section: Discussionsupporting
confidence: 71%
“…For Sakhalin, the signature of repeated migrations from the continent has also been suggested for the brown bear and the mountain hare, indicating that the migration to Sakhalin from the continent occurred after the establishment of the Hokkaido lineage (Kinoshita et al 2012;Hirata et al 2013). The gray red-backed vole, Korean field mouse, and least shrew may also have exhibited at least 2 migrations onto the island of Sakhalin (Pavlenko 1989;Iwasa et al 2000;Serizawa et al 2002;Sakka et al 2010;Abramson et al 2012;Ohdachi et al 2012). The similar pattern of coexistence of old and recent migrants in Sakhalin was also observed for the Siberian salamander (Matsui et al 2008;Poyarkov and Kuzmin 2008;Malyarchuk et al 2011Malyarchuk et al , 2013 and the carrion crow (Kryukov et al 2012).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…latronum has previously been regarded as a valid species (Allen 1940;Zimmermann 1962;Corbet and Hill 1992;Musser and Carleton 1993;Musser et al 1996;Musser and Carleton 2005), and in 2010, based on molecular data, Sakka et al (2010) found that 'the phylogeographic pattern observed in A. latronum demonstrated strong differentiated populations in the Sichuan and Yunnan regions' (Sakka et al 2010). In the present study, the results of principal component analyses (Figures 2 and 3) showed that the specimens of A. latronum (obtained from 18 sampling areas in southwestern China) cluster into two distinct geographic groups: A. latronum lijiangensis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the polarized secretory cells of salivary glands have been used as a model for studying evolutionary diversity at the cellular level (Phillips & Tandler, 1987;Tendler et al, 1988). The Korean striped field mouse, Apodemus agraius belonging to Rodentia is the most common small mammal inhabiting woodlands and forests throughout the Korean peninsula (Kim et al, 2000;Kim & Park, 2012;Sakka et al, 2010;Yoon et al, 1997). Intensive research on ecology, systematics and genetics of these animals within natural populations has been reported from many perspectives (Kim et al, 2000;Kim & Park, 2012;Yoon et al, 1997).…”
Section: Introductionmentioning
confidence: 99%